Reproductive Performance of Piptanthus nepalensis along an Elevation Gradient in Central Nepal - Paudel, Babu Ram; Subedi, Chandra Kanta (Himalayan Biodiversity, 2023)
Assessing altitudinal variation in the reproductive outputs of a plant species provides important insights into the reproductive adaptation of plants towards stressful environmental conditions. However, such studies are yet meager, particularly with reference to Nepalese plants. In this study, we assessed the variation in the reproductive performance of Piptanthus nepalensis along the elevation gradient in central Nepal. We considered ovule production, seed production per fruit, seed set proportion, ovule/seed abortion proportion, and individual seed mass as the various proxies of reproductive performance of P. nepalensis and estimated those traits at six sites from 3225 m to 3610 m asl within Gaurishankar Conservation Area, Dolakha, Nepal. We tested if the various reproductive performance traits of P. nepalensis were correlated with elevation. We also tested if an individual seed mass of P. nepalensis was correlated with an intrinsic factor, seed number per fruit. The result revealed that most of the studied reproductive performance traits were not related to the elevation. Moreover, individual seed mass also did not show a correlation with seed number per fruit. The almost independent relationship of important reproductive outputs of P. nepalensis with elevation and seed number per fruit thus suggest that this plant species could endure wide ranges of abiotic and intrinsic stresses for achieving optimal reproductive performance and survivorship.